“Implementación de un Sistema de Control Interno en la Cooperativa de Transporte Sur Oriente de la Ciudad de Loja Periodo 2020-2021 - Silverio Gonzaga, Elian Manuel (2023)
The present work of curricular integration called: IMPLEMENTATION OF AN INTERNAL CONTROL SYSTEM IN THE COOPERATIVE OF TRANSPORTATION SOUTH EAST OF THE CITY OF LOJA PERIOD 2020-2021, has been proposed and developed under the guidelines of the National University of Loja as a prerequisite for obtaining the degree of Bachelor in Accounting and Auditing. Nowadays, the design and implementation of internal control systems is very important due to the globalization that surrounds large, medium and small companies, forcing top management to implement process activities that allow measuring performance and making timely decisions to achieve the goals set by the organization. In this context, the research work has been developed with the general objective of implementing an internal control system for the Cooperativa de Transporte Sur Oriente of the city of Loja, through the application of specific procedures to achieve an adequate administrative and accounting management, for the fulfillment of the same internal control questionnaires were applied in accounting and administrative area in order to determine the current situation of the organization, the SWOT matrix was applied which served to establish strategies for the cooperative, after this, internal control procedures were provided for the activities carried out by the company. That is why the methodology used for the development of the research began with the use of internal control questionnaires, determination of the Strengths, Opportunities, Weaknesses and Threats, management indicators, and as a final part, clear procedures were established for the activities that the entity develops in the accounting and administrative area. As a result of the study, it was defined that not having an internal control system has the consequence that the activities performed by the organization are not carried out correctly, thus causing low levels of efficiency and effectiveness in its accounting and administrative operations. Finally, it is suggested that the cooperative's management and administration adopt the proposal proposed in order to develop their activities based on internal rules, controls and regulations.